Avelumab first-line maintenance in locally advanced or metastatic urothelial carcinoma: Applying clinical trial findings to clinical practice. (June 2021) - Grivas, Petros; Agarwal, Neeraj; Pal, Sumanta; Kalebasty, Arash Rezazadeh; Sridhar, Srikala S.; Smith, Jodi; Devgan, Geeta; Sternberg, Cora N.; Bellmunt, Joaquim
Highlights: Urothelial carcinoma (UC) can be chemotherapy sensitive and immunogenic. Immunogenic effects of chemotherapy support an immunotherapy maintenance strategy. Avelumab maintenance significantly prolonged overall survival in a phase 3 trial. Guidelines recommend avelumab as 1L maintenance for nonprogressed advanced UC. Avelumab prolongs overall survival across patient subsets and is well tolerated. Abstract: Although urothelial carcinoma (UC) is considered a chemotherapy-sensitive tumor, progression-free survival and overall survival (OS) are typically short following standard first-line (1L) platinum-containing chemotherapy in patients with locally advanced or metastatic disease. Immune checkpoint inhibitors (ICIs) have antitumor activity in UC and favorable safety profiles compared with chemotherapy; however, trials of 1L ICI monotherapy or chemotherapy + ICI combinations have not yet shown improved OS vs chemotherapy alone. In addition to direct cytotoxicity, chemotherapy has potential immunogenic effects, providing a rationale for assessing ICIs as switch-maintenance therapy. In the JAVELIN Bladder 100 phase 3 trial, avelumab administered as 1L maintenance with best supportive care (BSC) significantly prolonged OS vs BSC alone in patients with locally advanced or metastatic UC that had not progressed with 1L platinum-containing chemotherapy (median OS, 21.4 vs 14.3 months; hazard ratio, 0.69 [95% CI, 0.56–0.86]; P = 0.001). Efficacy benefits were seen across various subgroups, including recipients of 1L cisplatin- or carboplatin-based chemotherapy, patients with PD-L1+ or PD-L1− tumors, and patients with diverse characteristics. Results from JAVELIN Bladder 100 led to the approval of avelumab as 1L maintenance therapy for patients with locally advanced or metastatic UC that has not progressed with platinum-containing chemotherapy. Avelumab 1L maintenance is also included as a standard of care in treatment guidelines for advanced UC with level 1 evidence. This review summarizes the data that supported these developments and discusses practical considerations for administering avelumab maintenance in clinical practice, including patient selection and treatment management.